Navigating Challenges in Nursing Education: Lived Experiences of Clinical Instructors Supporting Students with Health Needs - Magtagñob, Joselle; Tabor, Vheendil; Tapel, Alpha; Gianan, Jeric; Alberto, Heigie (Alta Dharma Publisher, 2025)
Background: Clinical instructors play a vital role in supporting students with health needs by adapting teaching strategies, fostering an inclusive learning environment, and addressing unique challenges to ensure their academic and professional success. Objective: This study explores the lived experiences of nursing educators and clinical instructors at Catanduanes State University in supporting students with health needs. It aimed to identify challenges, evaluate teaching methods, and develop recommendations to improve inclusivity and resilience for students with health conditions in nursing education. Method: Using a qualitative phenomenological approach. Result: ten participants provided insights into challenges such as limited resources, insufficient training, and difficulty adapting teaching methods. While traditional teaching strategies were found inadequate, opportunities emerged through inclusive education, innovative practices, and collaborative learning environments. Educators emphasized the need for universal design for learning, simulation-based training, and tailored assessments to better accommodate diverse student needs. Recommendations: It include ongoing professional development, enhanced assistive technologies, and flexible teaching plans to create a more inclusive educational system. These findings aim to guide future strategies and policies, ensuring nursing education adapts to meet the varied needs of both students and the healthcare sector.